An Expert System to Estimate the Capacity of Harvesting Energy from Biogas and Its Capacity in TRNC - Onder, Hasan H. (IEEE Computer Soc, 2009)
In TRNC, the electricity is been obtained from fuel oil, which is most expensive production in the world. The aim of this research is to produce electricity from biogas to reduce the cost of electricity in TRNC. Our researches proved that the potential of electricity from biogas is 1/5-1/3 of total electricity consume in TRNC. In addition, when biogas is used to produce electricity, there is the added potential for harvesting hot water and steam from the engine's exhaust and cooling systems. Combining hot water and steam recovery with electricity generation may provide an overall conversion efficiency of 80% or more. Following the Methane gas extraction from the Manure and Farm waste, the remaining fermented manure turns out to be a lot more suitable for use as a fertilizer in the farm, and as a matter of fact its productivity efficiency in comparison to its original form is enhanced by at least 20% - 25%. The overall aim of this study was to investigate the use of Expert Systems to estimate the capacity of harvesting energy from biogas.
8th International Conference on Machine Learning and Applications -- DEC 13-15, 2009 -- Miami Beach, FL
Keywords: Expert system; Biogas; Capacity determination